EFFECTS OF IRRIGATION AND FERTILIZATION ON STEM DIAMETER GROWTH IN A MEDITERRANEAN HELM OAK FOREST - Mayor, X; Rodà, F (FOREST ECOLOGY AND MANAGEMENT, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for helm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a helm oak stand with a high density of stems of resprout origin (($) over bar x = 18275 stems ha(-1)), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week(-1) during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha(-1); (iii) phosphorus fertilization in a single application of 125 kg P ha(-1). Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (($) over bar x+/-SE 0.27+/-0.07 mm year(-1)), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P<0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of helm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.
Keywords: fertilization; Growth; irrigation; Stem diameter growth

Growth response of holm oak (Quercus ilex L) to commercial thinning in the Montseny mountains (NE Spain) - Mayor, X; Rodà, F (Ann. For. Sci., 1993)
Growth responses of holm oak (Quercus ilex) to commercial thinning were studied in the Montseny Biosphere Reserve (northeast Spain), where selection thinning for firewood production is currently the dominant form of management in holm oak forests. Thinning significantly increased mean stem diameter increment by 83% over that of unthinned plots during the 6-9-yr period after thinning, and by 48% from 9-12 yr after thinning. Absolute diameter increment was positively correlated with initial diameter at 1.30 m from the ground (dbh) both in thinned and unthinned plots. Thinning increased growth in large trees more than in smaller trees. Relative diameter growth was negatively correlated with initial dbh. It is concluded that individual holm oak stems in previously coppiced stands respond vigourously to thinning, and still do so 6-9 yr after thinning. The growth response diminishes 9-12 yr after thinning due to canopy closure. However, absolute rates of stand growth, as well as basal area and stem biomass increments, were unaffected by thinning during these time intervals, an example of density compensation.
Keywords: Canopy closure; Quercus ilex = holm oak; selection thinning; stand growth; tree growth

Is primary production in holm oak forests nutrient limited? - Mayor, X; Rodà, F (Plant Ecology, 1992)
Correlations between primary production and patterns of nutrient use and nutrient availability were investigated in 18 plots in closed holm oak (Quercus ilex L.) stands in the Montseny mountains (NE Spain), searching for evidence of nutrient limitation on primary production. The plots spanned a range of altitudes and slope aspects within a catchment. Nutrients considered were nitrogen (N), phospho- rus (P), potassium (K) and magnesium (Mg) in plant samples, and the above plus calcium (Ca) and sodium (Na) in the soil. Primary production was found by summing the annual aboveground biomass increment to the annual litterfall. Across plots, primary production was correlated with the annual re- turn of nutrients in litterfall, but this relationship probably arose from the common effects of the amount of litterfall on both primary production and nutrient return, and not from any nutrient limitation. Pri- mary production was not significantly correlated with nutrient concentrations in mature leaves nor leaf litterfall, nor with absolute or relative foliar retranslocation of nutrients before leaf abscission, nor with the concentration and content (kg/ha) of total N, extractable P, and exchangeable K, Mg, Ca and Na in the upper mineral soil. We conclude that there is no correlational evidence that primary production is nutrient limited in this holm oak forest.
Keywords: biomass increment; litterfall; nutrient availability; nutrient cycling; Quercus ilex